Artistic and Scientific Activity of Andrij Hornjatkevyč (Canada) in the Context of Bandura Art Development in Ukraine and Among Diaspora - Violetta Dutchak (Вісник Київського національного університету культури і мистецтв. Серія: Музичне мистецтво, 2018)
This article deals with generalized analysis of artistic and scientific activity by famous performer and researcher from Canada – Andrij Hornjatkevyč (Edmonton), in context of bandura art development in Ukraine and abroad. This article deals with the complex analysis of Andrij Hornjatkevyč 's multi-vectoral activity, based on the research and popularization of kobzar art of past and present times. The phases of his life path and professional development, activity in spheres of Ukrainian language research, Ukrainian oral and music folklore, traditions of authentic kobzar movement, popularization of epic kobzar repertoire are being pointed out, and this is the first time for the information to be entered in scientific circulation as introductory research.